2021
DOI: 10.1007/s10551-021-04873-6
|View full text |Cite
|
Sign up to set email alerts
|

Pledging Patent Rights for Fighting Against the COVID-19: From the Ethical and Efficiency Perspective

Abstract: In response to the great crises of the COVID-19 coronavirus, virtually all new technologies protected by patent rights have been used in practice from diagnostics, therapeutic, medical equipment, and vaccine to prevention, tracking, and containment of COVID-19. However, the moral justification of patent rights is questioned when pharmaceutical patents conflict with public health. This paper proposes a revised approach of deciding on how to address the conflicts between business ethics and patent protections an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Although this issue is very interesting, its feasibility is particularly complex and intricate. Accordingly, there are discordant opinions among scholars and physicians on the real usefulness of patent liberalization (3)(4)(5)(6). It has been suggested that an exception be made to the agreements establishing the World Trade Organization, in particular The Agreement on Trade Related Aspects of Intellectual Property Rights.…”
Section: Introductionmentioning
confidence: 99%
“…Although this issue is very interesting, its feasibility is particularly complex and intricate. Accordingly, there are discordant opinions among scholars and physicians on the real usefulness of patent liberalization (3)(4)(5)(6). It has been suggested that an exception be made to the agreements establishing the World Trade Organization, in particular The Agreement on Trade Related Aspects of Intellectual Property Rights.…”
Section: Introductionmentioning
confidence: 99%
“…Healthdriven, voluntary, non-exclusive, transparent, and open licenses were supplied for sharing data and information on COVID-19 treatment, diagnosis, vaccines, and other cutting-edge health technologies. Pioneers of COVID-19 life-saving tools can boost manufacturing ability and extend access to health products in all regions (52).…”
Section: Socialmentioning
confidence: 99%
“…The idea of a patent waiver for the COVID vaccine is not sweet for developed nations and pharma companies. It is an obvious notion of the pharma industry that why expensive technology could be made available to competitors for a cheaper price 8 . It's high time to consider a patent reprieve for COVID-19 vaccines.…”
Section: Reviewarticlementioning
confidence: 99%